(untitled) (Journal of Architectural Design, 2023)
Geopolymer is an environmentally benign substance that may be utilized as a concrete repair material, a structural element in a building, or as a whole in construction. This paper presents an experimental study on the shear transfer of geopolymer concrete under monotonic and repeated loads. Ten push-off specimens with and without reinforcement across the shear plane were cast and evaluated. The geopolymer concrete was used in the first five push-off specimens, whereas the conventional concrete was used as a reference in the last five. The proposed push-off specimen was 500mmx250mmx125mm in size. Shear stress, vertical slip, and horizontal separation at the shear plane were measured for each load increment up to failure. To determine the vertical slip and horizontal separation at the shear plane, two-stroke linear variable displacement transducers (LVDT) were utilized. The shear strength of geopolymer concrete was found higher than that of conventional concrete in the tests. In addition, vertical slip and horizontal separation were smaller in geopolymer concrete than in conventional concrete